Workshop Technological Pedagogical Content Knowledge (Tpack) Berbasis Literasi Sains: Kompetensi Guru Ipa Abad 21 Dan New Normal - Permanasari, Anna (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
A teacher is an educator who must master learning competencies consisting of pedagogical, professional, social and individual competencies. These competencies are used by teachers to encourage improving the quality of learning in the classroom. This study aims to analyze TPACK on scientific literacy skills in students' science learning. This research is a type of research with quantitative methods with meta-analysis methods. The Technological Pedagogical Content Knowledge Workshop based on Science Literacy: 21st Century Science Teacher Competencies and the New Normal in Bogor City was attended by 30 participants. The results obtained from this activity are a technology-based Learning Implementation Design and science literacy to be used in science learning in grades VII, VIII, and IX.